Social Support and Resilience among Street Children: A Cross-Sectional Study in Semarang, Indonesia - Dayat Trihadi; Siti Yuliana; Sri Hartini (Pusat riset dan Inovasi Nasional, 2024)
Street children constitute a highly vulnerable population who spend most of their time in public spaces working in the informal sector and are at increased risk of engaging in deviant behaviours. Social support and resilience are recognised as key protective factors that may enable street children to adapt to adversity. This quantitative study employed a cross-sectional correlational design to examine the association between social support and resilience among street children in Semarang City, Indonesia. A total of 42 street children were recruited using accidental sampling. Data were collected using modified Likert-type questionnaires measuring social support (social embeddedness, enacted support, and perceived support) and resilience (emotion regulation, impulse control, causal analysis, self-efficacy, realistic optimism, empathy, and reaching out). Data were analysed using univariate statistics and Spearman’s rank correlation test. Most respondents reported moderate levels of social support (90.48%) and resilience (66.67%). Spearman’s test indicated a significant, positive, yet low correlation between social support and resilience (p = 0.014; r = 0.228). These findings suggest that higher social support is associated with greater resilience, although other internal and external factors are likely to contribute to resilience among street children.